Equine chorionic gonadotropin treatment and timed artificial insemination for dairy cow production under heat stress - Daisuke FUNAKOSHI; Hidetoshi SHIOTANI; Makoto SEKI (The Society for Reproduction and Development, 2023)
This study investigated the effects of timed artificial insemination (TAI) and equine chorionic gonadotropin (eCG) administration on lactating dairy cows under heat-stress conditions (average temperature-humidity index: 80). Timed artificial insemination was performed on the cows with (n = 57) or without (control, n = 41) supplementation with 500 IU of eCG at the day of PGF2α treatment using the CIDR-Ovsynch protocol. GnRH was administered, and a progesterone device (CIDR) was inserted on Day −10 of the treatment protocol. The CIDR was removed on Day −3, and the cows were treated with PGF2α. Two days later, a 2nd GnRH injection was administered. Subsequently, AI was performed on Day 0 (16-20 h after the 2nd GnRH injection), and pregnancy was diagnosed on Days 32 and 60. Plasma progesterone (P4) concentrations were measured after AI. Results showed that the eCG group had a higher pregnancy per AI (P/AI) than the control group (43.9 vs. 12.2%, P = 0.002), which was also accompanied by elevated P4 levels. Four cows in the eCG group had multiple calves, representing 7.0 and 16.0% of the group and pregnant cows, respectively. In conclusion, 500 IU of eCG combined with CIDR-Ovsynch in lactating dairy cows under severe heat stress conditions successfully improved fertility. However, the protocol may have a slight risk of multiple births.